2012
DOI: 10.1366/11-06535
|View full text |Cite
|
Sign up to set email alerts
|

Remote Raman Spectroscopy for Planetary Exploration: A Review

Abstract: In this review, we discuss the current state of standoff Raman spectroscopy as it applies to remote planetary applications, including standoff instrumentation, the technique's ability to identify biologically and geologically important analytes, and the feasibility to make standoff Raman measurements under various planetary conditions. This is not intended to be an exhaustive review of standoff Raman and many excellent papers are not mentioned. Rather it is intended to give the reader a quick review of the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 72 publications
(151 reference statements)
0
69
0
2
Order By: Relevance
“…outside, during daylight) [74]. The retrieval of information from a remote distance not only removes the need for rover relocation (saving time, power and other resources) but also allows the exploration of what would normally be inaccessible regions of a planet [35]. In fact, in addition to the prospect of deploying a stand-off Raman instrument on Mars, a recent Science Definition Report has identified Raman analysis as a key element in the exploration of Europa [76], and it is reported that a stand-off Raman instrument, similar to existing prototypes, would be capable of measuring and identifying various salts, organic and CO 2 ice on the surface of Europa, potentially to a depth of a few centimetres [77].…”
Section: (B) Stand-off Ramanmentioning
confidence: 99%
“…outside, during daylight) [74]. The retrieval of information from a remote distance not only removes the need for rover relocation (saving time, power and other resources) but also allows the exploration of what would normally be inaccessible regions of a planet [35]. In fact, in addition to the prospect of deploying a stand-off Raman instrument on Mars, a recent Science Definition Report has identified Raman analysis as a key element in the exploration of Europa [76], and it is reported that a stand-off Raman instrument, similar to existing prototypes, would be capable of measuring and identifying various salts, organic and CO 2 ice on the surface of Europa, potentially to a depth of a few centimetres [77].…”
Section: (B) Stand-off Ramanmentioning
confidence: 99%
“…Raman spectrometers have been proposed for exploration of a diverse range of extraterrestrial targets including asteroids, [1] Europa, [2,3] Mars, [4][5][6] the Moon, [7] and Venus. [8] A Raman laser spectrometer (RLS) is part of the science instrument payload of the European Space Agency 2018 ExoMars mission; the RLS instrument will target mineralogical and astrobiological investigations on the surface and subsurface of Mars.…”
Section: Introductionmentioning
confidence: 99%
“…Its wide applicability comes from the fact that each band in a Raman spectrum represents interaction of incident light with a vibrational mode in the molecule or crystal; it is therefore highly material specific and can be used for identification and structural characterization of unknown samples. For planetary science, laser Raman spectroscopy offers an attractive in situ method for robotic exploration of planetary surfaces that can combine capabilities for the identification of minerals present in geological materials, with capabilities to detect organic matter [9][10][11][12][13][14]. Additionally, Raman is a nondestructive technique that requires no sample preparation and is well suited for deployment on a planetary rover or lander.…”
Section: Introduction a Raman Spectroscopy For Planetary Sciencementioning
confidence: 99%